Unmasking Vitamin B12 Deficiency Misdiagnosed as Myelodysplastic Syndrome - Maria Jamil; Zeinab Nasser; Dawood Jamil; Jawad Z. Sheqwara (Case Reports in Hematology)
Conclusion: Our case series highlights the importance of ruling out alternative causes of dysplasia in MDS when solely morphological abnormalities are observed on a bone marrow biopsy. It also underscores the crucial aspect of assessing MMA and homocysteine levels in individuals with normal vitamin B12 levels when there is a high clinical suspicion of B12 deficiency.